Automation and the jobs of young workers - Guillermo Falcone; Irene Brambilla; Andrés César; Leonardo Gasparini (Latin American Economic Review, 2022)
New automation technologies affect workers in a heterogeneous manner according to their demographic characteristics, skills, and the tasks they perform. In this paper we study the effects of automation on labor market outcomes in a developing country, Chile. We focus our analysis on the heterogeneous impacts of automation across cohorts. Does automation affect young workers differently than older workers? Do young workers tend to perform routine tasks? Are young workers in routine occupations more exposed to negative effects of technology? Our empirical strategy is based on exploiting differences in the routinization of tasks across districts and occupations and a change in the trend of automation technology adoption in Chile. We find that young workers are more easily displaced by automation than older workers of similar characteristics. At the same time, cohorts of young workers are more skilled and more mobile than older workers, which implies that they have good prospects of working in complement with automation technology in the near future. The young and unskilled are the most vulnerable group of workers.
Keywords: 330; technology adoption; automation; labor markets; young workers; age groups; unemployment; wages; occupations; tasks; routinization